Knowledge, willingness to provide service and preparedness for monkeypox infection among medical practitioners working in Bangladesh: a multicentred cross-sectional study - Mohammad Jahid Hasan; Salwa Islam; Mir Susmita Zaman; Jannatul Fardous; Shehab Uddin Al Abid; Tamanna Tabassum; Monirul Hasan; Mohiuddin Sharif (BMJ Public Health)
Background The resurfaced zoonotic disease, Monkeypox, has become a global public health concern recently. Therefore, the objective of this study was to assess the current knowledge, willingness to provide service during an outbreak and preparedness about human monkeypox among medical practitioners in Bangladesh.Methods This cross-sectional study was conducted among registered physicians at the three medical college hospitals in Dhaka, Bangladesh. Knowledge about monkeypox was assessed by 20 questions, collected through a self-answered paper-based structured questionnaire. Good knowledge was defined by 70% of correct responses among the asked questions. Willingness and preparedness to treat during the monkeypox outbreak were also assessed. Multivariate logistic regression analysis was performed to assess the predictors of good knowledge of monkeypox infection. Statistical analysis was done with SPSS V.25.0.Result Out of 385 physicians, two-thirds (63%) were male, and between 31 and 50 years of age (58%). A majority (91.4%) knew monkeypox is transmitted human-to-human, followed by sexual (55.1%) and vertical transmission (34.8%), but only 19.5% were aware of vaccine availability. Overall, about half of the respondents (57%) showed a good knowledge of monkeypox and the remainder (43%) had poor knowledge. Older age, higher education and having a higher job designation were found to be associated with good knowledge. However, only 30.1% expressed willingness to provide care, and just 22.3% believed their hospitals were prepared for a potential outbreak.Conclusion The present study highlighted that physicians in Bangladesh possess a relatively good level of knowledge, with a lack of practical preparedness and willingness to serve in managing monkeypox cases during an outbreak.